2006
DOI: 10.3168/jds.s0022-0302(06)72231-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Corn Silage Hybrid and Metabolizable Protein Supply on Nitrogen Metabolism of Lactating Dairy Cows

Abstract: This experiment was conducted to determine the effects of corn silage hybrid and supply of metabolizable protein (MP) on manure excretion and N metabolism by lactating dairy cows. Eight Holstein cows in midlactation (replicated 4 x 4 Latin square with 21-d periods) were fed 1 of 4 treatments, arranged factorially. Diets contained 55% corn silage made from a dual-purpose hybrid or a brown midrib (BMR) hybrid, and 45% concentrate that contained either a low or high concentration of rumen undegradable protein (al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 29 publications
7
37
2
2
Order By: Relevance
“…The CP content of the DP and bm3 corn silages was similar (9.2% DM) but DP had greater NDF (42.3 ± 5.1 %) and lignin (3.5 ± 0.2 %) content compared with bm3 (NDF = 40.2 ± 3.0 %; lignin = 2.4 ± 0.30%). The lower lignin content of bm3 was expected and was similar to that reproted previously (Oba and Allen, 2000a;Weiss and Wyatt, 2006). As expected, in vitro estimates of NDF digestibility following a 30-h incubation (Table 2) were greater for bm3 corn silage compared with DP corn silage (61.0 vs. 49.1 ± 0.62%), with this difference being similar to that of others (Ebling and Kung, 2004).…”
Section: Experimental Measuressupporting
confidence: 69%
See 3 more Smart Citations
“…The CP content of the DP and bm3 corn silages was similar (9.2% DM) but DP had greater NDF (42.3 ± 5.1 %) and lignin (3.5 ± 0.2 %) content compared with bm3 (NDF = 40.2 ± 3.0 %; lignin = 2.4 ± 0.30%). The lower lignin content of bm3 was expected and was similar to that reproted previously (Oba and Allen, 2000a;Weiss and Wyatt, 2006). As expected, in vitro estimates of NDF digestibility following a 30-h incubation (Table 2) were greater for bm3 corn silage compared with DP corn silage (61.0 vs. 49.1 ± 0.62%), with this difference being similar to that of others (Ebling and Kung, 2004).…”
Section: Experimental Measuressupporting
confidence: 69%
“…As a consequence of improved fiber digestibility, the amount of available energy may be greater for cows consuming bm3 corn silage compared with those consuming conventional hybrids. However, the extent of energy utilization may be limited because cows fed bm3 silage usually consume more feed (Oba and Allen, 1999;Tine et al, 2001), thus reducing total diet digestibility (Weiss and Wyatt, 2006). Several studies have reported that cows consumed more feed when fed bm3 corn silage compared with an isogenic control (Oba and Allen, 1999;Greenfield et al, 2001;Tine et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies reported a decrease in ruminal pH when BMR was fed Taylor and Allen 2005;Gehman et al 2008). This may have been caused by the increased supply of fermentable substrate in the rumen due to enhanced NDF digestibility of BMR (Weiss and Wyatt 2006).…”
Section: Ruminal Fermentation Characteristicsmentioning
confidence: 99%